Structural notch effect in steel-welded joints - Bilous, Pawel; Lagoda, Tadeusz (Welding international, 2012)
In this paper, stress concentrations occurring in welded joints were described. Methods of fatigue life determination in welded joints were presented. Moreover, the paper contains descriptions and methods for determining the notch effect coefficient K f . Curves presenting histories of the fatigue coefficient of the structural notch effect were plotted for a double-V butt weld and some selected steels, based on strain analysis.